Հայկական վերածննդի երաժշտաբանաստեղծական արվեստի որոշ բնութագրիչներ՝ Ս․ Ներսես Շնորհալու ժառանգության մեջ - Նավոյան, Մհեր
The musical and poetic reinterpretation of pre-Christian culture is characteristic of the works of St. Nerses Shnorhali. Along with this pre-Christian inheritance, the saint’s work was strongly influenced by two important aspects of Armenian Renaissance thought: specifically, the philosophy of Dionysius the Areopagite and Neoplatonism. Evidence of this Neoplatonic proclivity is found everywhere throughout his oeuvre, most clearly manifesting in some hymns of the Horologion and Missale. Among them, Doxology, from the latter book, occupies a special place. The introduction of a secular artform, the Armenian epic musical tradition, into medieval professional music, and its continued reinterpretation, combined with the significant impact of the philosophy of pseudo-Dionysius the Areopagite and Neoplatonism, thus resulting in the emergence of new artistic forms. As a result, various new song genres emerged, and a new form of musical theory was developed, an antipode to medieval modal thinking. These occurrences became one of the primary features of the Armenian Renaissance (their mature manifestations covered the 10th-12th centuries). The most significant phase in this intellectual development is represented by the work of St. Nerses Shnorhali. Характерное для творчества Св. Нерсеса Шнорали музыкально-поэтическое переосмысление явлений дохристианской культуры сочетается в его наследии с другим важнейшим признаком армянского Возрождения – идеями Псевдо-Дионисия Ареопагита и неоплатонизма. Они встречаются в его наследии повсеместно, ярче всего проявившись в ряде гимнов Часослова и Миссала. Особое место среди последних занимают Славословия. С другой стороны, проникновение и переосмысление светского искусства, в частности армянской эпической музыкальной традиции в армянском средневековом профессиональном музыкальном искусстве, а также мощное влияние, оказанное на него идеями Псевдо-Дионисия Ареопагита и неоплатонизма, привели к формированию новых реалий. Так, образовался комплекс новых песенных жанров, сложилась новая форма музыкального мышления, противоположная средневековому гласовому мышлению. Эти явления стали одними из основных характеристик армянского Возрождения, зрелые проявления которого охватывают X-XII вв. Творчество Св. Нерсеса Шнорали представляет собой важнейший этап в формировании этих реалий.
Keywords: Հայկական Վերածնունդ